Efficacy of a Local Isolate of Metarhizium pinghaense Against Females of Margarodes prieskaensis (Homoptera: Coccoidea) in Field Trials - Allsopp, Elleunorah; Erasmus, Talitha; Mathulwe, Letodi L.; Stokwe, Nomakholwa F. (South African Journal of Enology and Viticulture, 2024)
The indigenous soil-dwelling scale insect, Margarodes prieskaensis, can severely damage and even kill grapevines in the northern grape-growing regions of South Africa. There are no registered means of control, and soil applications of insecticides raise environmental concerns. Using local isolates of entomopathogenic fungi (EPF) that are better adapted to local conditions to target female margarodes could add a valuable biocontrol component to an integrated management strategy. The objective of this research was to evaluate the efficacy of a local isolate of Metarhizium pinghaense against M. prieskaensis females under field conditions. Dry conidia suspended in water and 0.05% v/v Tween 20, applied as a soil drench, achieved 19.1% and 17.7% infection of margarode females in the Northern Cape and Limpopo, respectively, in 2021. Conidia stored in canola oil, suspended in water and 0.05% v/v Tween 20 and applied as a soil drench achieved infection rates of 38.5% and 62.8%, respectively, at the same sites in 2022. These results confirm the importance of formulating conidia for protection against adverse environmental conditions to improve EPF efficacy in the field. This study is the first to demonstrate the efficacy of M. pinghaense against margarode females at the soil surface and confirms the potential of this EPF for the biological control of margarodes.